A NEW WEED MANAGEMENT APPROACH TO IMPROVE SOIL HEALTH IN A TROPICAL PLANTATION CROP, RUBBER (HEVEA BRASILIENSIS). (17th February 2015) - ABRAHAM, JOSHUA; JOSEPH, PHEBE
SUMMARY: The soil health of rubber ( Hevea brasiliensis ) plantations shows a declining trend, mainly due to the continuous mono crop cultivation and the 'clean-weeding' practices. Another weeding approach which allows the under-flora to grow profusely after closing up of the rubber canopy (no-weeding) can establish a multi-flora system that can improve soil health. A case study was undertaken to test this hypothesis. Rubber fields with and without control of under-flora were investigated for different soil properties, biomass and nutrients of under-flora and rubber yield. The 'no-weeding' practice for about 10 years in the rubber fields significantly improved the soil OC, N, available forms K and Mg, respiration rate and moisture status. The biomass and associated nutrients of under-flora also were much higher while the rubber yield was not negatively affected in the 'no-weeding' fields. The new weed management system is of great significance in improving soil quality, carbon sequestration and biodiversity conservation, besides the economic and energy savings without affecting crop yield.